Pengaruh Pembelajaran Klasikal terhadap Asesmen Kognitif dengan Motivasi sebagai Variabel Moderasi pada Pembelajaran Mesin CNC SMK Negeri 3 Tanjungpinang. - Fitrinaldi Fitrinaldi; Encik Abdulhajar; Samsul Hadi; Desi Rahmatina; Nur Izzati; Leni Aria (Badan Perencanaan, Penelitian dan Pengembangan Pemerintah Provinsi Kepulauan Riau, 2025)
Abstrack : This study analyzes the effectiveness of classical learning methods on students' cognitive assessments, considering the role of motivation as a moderating variable. This study uses a quantitative experimental design on students from SMK Negeri 3 Tanjungpinang. The research results indicate that classical learning has an insignificant negative impact on students' cognitive assessment. Student motivation shows a significant impact, both directly and through interaction with cognitive assessment, substantially improving learning outcomes. An R Square value of 97.9% indicates that the variation in cognitive assessment is predominantly explained by the motivation variable and its interactions. These findings underscore the importance of designing learning experiences that consider motivational factors to enhance student engagement and performance. A contextual approach based on technology and adaptive strategies is recommended to address the limitations of classical methods in improving cognitive outcomes. Keywords: Classical learning, student motivation, cognitive assessment, vocational education, adaptive strategies.